Estimação do desconto de reequilíbrio ótimo em concessões rodoviárias através da metodologia das opções reais - Coimbra, Mateus Rodrigues (2015)
These work proposes a methodology to evaluate in discrete time the 'reequilibrium discount', a mechanism of balance between govern and business interests, in highways contracts, by using Classical Theory Concepts and Real Options Theory. The model developed permits to incorporate flexibilities related to uncertainties, like managerial decisions, biased behaviors, and risks associated to political decisions, commonly presents in highway concessions contracts in Brazil.